Joseba Gabilondo. Introduction to A Postnational History of Contemporary Basque Literature (1978-2000): Remnants of the Nation. Tamesis, 2019. - Belén Rodríguez Mourelo (Studies in 20th & 21st Century Literature, 2022)
Review of Joseba Gabilondo. Introduction to A Postnational History of Contemporary Basque Literature (1978-2000): Remnants of the Nation. Tamesis, 2019. xii +338 pp.
Keywords: Basque literature; postnational; Bernardo Atxaga; Kirmen Uribe